Retroperitoneoscopic donor nephrectomy with a gel-sealed hand-assist access device - Arai, Kei (BioMed Central, 2013)
BACKGROUND: The hand-assisted technique enables the rapid extraction of the graft, shortening the warm ischemia time (WIT), and the retroperitoneoscopic approach is potentially associated with a less incidence of postoperative ileus in donor nephrectomy for living kidney transplantation. The aim of this study was to assess the efficacy and safety of retroperitoneoscopic donor nephrectomy with a gel-sealed hand-assist access device (GelPort), which is a wound sealing device that permits the access of the hand to the surgical field, free trocar site choice within it, and rapid conversion to open surgery if necessary, while preserving the pneumoperitoneum/pneumoretroperitoneum. METHODS: Seventy-five consecutive donors receiving this procedure were retrospectively studied. A 2-cm skin incision was made at the midpoint between the tip of the 12th rib and superior border of the iliac bone in the midaxillary line, through which retroperitoneal space was made. Preperitoneal wound with a 6 – 7-cm pararectal incision in the upper abdominal region was connected to the retroperitoneal space. A GelPort was put inside the pararectal surgical wound. The principle was pure retroperitoneoscopic surgery; hand-assist was applied for retraction of the kidney in the renal vessel control and graft extraction. RESULTS: The mean operation time including waiting time for recipient preparation was 242.2±37.0 (range: 214.0–409.0) min, and the mean amount of blood loss was 164.3±146.6 (range: 10.0–1020.0) ml. The mean WIT was 2.8±1.0 (range: 1.0–6.0) min. The shortage of renal vessels or ureter was observed in none of the grafts. No donor experienced blood transfusion, open conversion, or injury of other organs. Blood loss was greater in patients with body mass index (BMI) of 25 kg/m(2) or higher than in those with BMI of <25 kg/m(2) (218.4±98.8 vs. 154.8±152.1 ml, P=0.031). No donor had postoperative ileus or reported wound pain leading to decreased activity of daily life or wound cosmetic problem. CONCLUSIONS: Retroperitoneoscopic hand-assisted donor nephrectomy with the mentioned approach was suggested to be a feasible option without compromising safety, although further improvement in surgical techniques is warranted.